PERBANDINGAN METODE BACKWARD DAN FORWARD PADA SELEKSI MIXED-EFFECTS MODEL: ANALISIS FRAGILE STATE INDEX ASIA TENGGARA - Mega Maulina; Madona Yunita Wijaya; Nina Fitriyati (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
In the era of globalization, concerns about the stability and vulnerability of nations have become a primary focus in the field of international relations research. One of the indicators measuring a country’s vulnerability is the Fragile State Index. This research discusses the analysis of Fragile State Index in Southeast Asian countries using panel data observed from 2010 to 2021, focusing on economic impacts. The factors involved include Gross Domestic Product, General Government Net Lending/Borrowing, Inflation, and Life Expectancy. A mixed-effects model is employed to examine the influence of economic factors on the Fragile State Index. The selection of the best model is carried out by comparing Backward Elimination and Forward Selection procedures. The research findings indicate that the best model for interpreting the influence of economic factors on the Fragile State Index is the one using the Backward Elimination method. Significant variables in this model include Gross Domestic Product, General Government Net Lending/Borrowing, Life Expectancy, and the interaction between General Government Net Lending/Borrowing and Inflation